Board-Game based Nutrition Education enhanced Breakfast Habit of In-School Adolescents in Ile-Ife, Nigeria (African Journal of Biomedical Research, 2022)
This study was designed to assess the effect of board game-based nutrition education on breakfast knowledge, attitude and habit of in-school adolescents in Ile-Ife, Nigeria. The quasi-experimental study involved 360 in-school adolescents assigned into Participatory Experimental (PEG), Experimental (EG) and Control groups (CG) of 120 each. An interviewer-administered questionnaire was used to collect information on respondents’ basic characteristics as well as knowledge, attitude and practices on breakfast consumption. A ‘Breakfast Master’ board game, developed with PEG was used for a 3-week intervention period among the experimental groups. Knowledge was assessed using 11-point scale, categorized as good (≥9) or poor (